OUTCOMES OF URETHRAL DILATION WITH AMPLATZ DILATORS IN THE MANAGEMENT OF URETHRAL STRICTURES - AHMAD , T; AYAZ , MM; BACHA , M; FARHAN , M; MOHAMMAD , F; GHAZANFAR , S (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the outcomes of urethral dilation with amplatz dilators in managing urethral strictures. We conducted this descriptive case series at multiple centers, including Waseem Medical Centre Batkhaila and Mercy Teaching Hospital Peshawar, from November 2022 to April 2023. A total of 30 male patients presented with urethral strictures were treated with urethral dilation using amplatz dilators. The outcomes assessed were maximum urinary flow and Post-void residual urine. Paired samples T-test was used for numerical variables. Mean age of patients was 64.87±11.96 years. Preoperative mean uroflowmetry flow (Qmax) was 8.6±2.97 mL/sec, while the PVR preoperatively was 198.4±59.19 mL. Qmax improved in 1st month at 18.87±2.64 mL/sec, in the 6th month at 17.50±2.99 mL/sec, and in the 12th month at 15.37±2.17 mL/sec (P = 0.0001). PVR improved in 1st month at 50.13±23.56 ml, 6th month at 64.47±23.31, and 12th month at 69.17±25.53 ml compared to the preoperative PVR (P = 0.0001). Urethral dilatation using amplatz renal dilators represents a technique that mitigates the inherent risks associated with blind dilatation methods. This approach is characterized by its safety, ease of application, high patient tolerance, and cost-effectiveness, rendering it a favorable alternative for treating urethral strictures.